Longitudinal analysis of an HLA-B*51-restricted epitope in integrase reveals immune escape in early HIV-1 infection. - Yager, N; Robinson, N; Brown, H; Flanagan, P; Frater, A; Fidler, S; Weber, J; Phillips, R (Wolters Kluwer Health, Inc, 2013)
OBJECTIVE: To fully define cytotoxic T-lymphocyte (CTL) escape variants of an HLA-B*51-restricted integrase epitope in early HIV-1 infection. DESIGN: Ninety-four longitudinally sampled acute/early HIV-1 subtype B-infected participants were assessed to determine HLA-B*51-restricted LPPVVAKEI (LI9) escape variants. METHODS: LI9 was sequenced at baseline and subsequent time points. Interferon-γ (IFNγ) ELISpot assays were performed using serial log dilutions of variant LI9 peptides to determine the cellular response and functional avidity. RESULTS: There is a significant association between HLA-B*51 expression and an evolving LI9 sequence from baseline to year 1 (P < 0.0001). We detected that the V32I and P30X polymorphisms emerged within HLA-B*51 participants over time. Reversion of the P30S polymorphism was observed by year 1 in one HLA-B*51 participant. LPPIIAKEI and LPSIVAKEI had significantly lower functional avidity compared with LPPVVAKEI and so may be less well recognized by LI9-specific CTLs; a positive IFNγ response to IPSVVAKEI was rarely seen. Functional avidity to wild-type LI9 inversely correlated with viral load (R = 0.448, P = 0.0485). CONCLUSION: Our results provide support for the role of HLA-B*51-restricted CTLs and functional avidity in the control of early HIV-1 infection.